USE OF FORMULATED FERTILIZERS FOR SOIL CHEMICAL PROPERTIES IMPROVEMENT AND OKRA (Abelmoschus esculentus L. Moench) YIELD IN IBUSA, DELTA STATE - Okole, P. A.; Ojobor, S. A.; Akparobi, S. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study evaluated the use of formulated fertilizers for soil chemical properties improvement and okra (Abelmoschus esculentus L. Moench) yield for two years in Ibusa, Delta State. The treatment consisted of six fertilizers (control (T1), NPK 15:15:15 fertilizer (T2), organic + NPK (T3), organic + N (T4), organic + PK (T5) and sole organic (T6)), while Clemson spineless okra variety was used to test the effectiveness of the fertilizers. Sawdust, rice bran, wood shavings, pig dung, cattle dung and poultry droppings were the materials used for organic fertilizer preparation. The organic and inorganic fertilizers were used to formulate the organo-mineral fertilizers at a ratio of 4:1 and 250kg/ha of NPK15:15:15 was applied, the organo-mineral fertilizers and organic manure were applied at 6tons/ha and 10tons/ha respectively. Randomized complete block design replicated three times was used for the study. Okra growth and yield parameters were measured from 2WAS-10WAS and soil samples were collected at harvest for routine analysis. Data collected were subjected to analysis of variance with R project for statistical computing to determine the treatment effects and means comparison was done with Turkey’s Honestly Significant Difference at P<0.05. Results showed that, the highest soil pH was obtained from T6 (5.80) and N from T4 (0.20%) in 2024 whereas P from T3 (23.30mg/kg) in 2023 and OM from T6 (1.98%) in 2024. T3 had the highest ECEC (8.87cmol/kg), T6 produced the highest okra yield(5.68ton/ha) that was closely followed by T4 (5.32tons/ha) in 2024, This is an indication that either organic or organo-mineral fertilizers could sustainably improve soil fertility and boost okra yield in tropical areas.